Analysis Of The Effectiveness Of The Internal Control System For Cash Receipts And Disbursements At The Modern Entreprenur Darul Musthofa Islamic Boarding School 2021-2022 - Fadilla Ayu Cahyani; Yenni Samri Juliati Nasution; Nurwani Nurwani (UNIVED Press, 2024)
This research aims to investigate the effectiveness of the internal control system for cash receipts and disbursements at entrepreneurial modern boarding school darul musthofa. The research employs a qualitative descriptive approach with the research subject is the Entrepreneurial Modern Boarding School Darul Musthofa. Data collection techniques including interviews, observations, and documentation. The findings indicate that the Modern Entrepreneurial Boarding School Darul Musthofa has successfully implemented an effective internal control system for cash inflow and outflow in line with accounting principles. The organizational structure, which segregates duties and responsibilities in cash handling, enhances accountability. Concrete steps such as digitization of records, regular monitoring, and authorization by the treasurer and head of the boarding school ensure accuracy, transparency, and efficiency in financial record-keeping. Structural separation, authorization, detailed recording, and risk monitoring through online financial transactions reflect the boarding school's commitment to modern financial management. The alignment of the internal control system with financial principles demonstrates sound practices. The treasurer's crucial role in ensuring the accuracy of financial records and the implementation of online financial transactions highlights the boarding school's innovative approach. Overall, the Modern Entrepreneurial Boarding School Darul Musthofa serves as a best practice example in financial management.